Pedoman dan Asesmen Manajemen Risiko Pada PT Logistik Nasional Tahun 2022-2023 - Putri, Alya Fellayati; Prasetyo, Aries Heru (Journal of Emerging Business Management and Entrepreneurship Studies, 2022)
PT Logistik Nasional is a multinational company that just started operating in Indonesia in 2018. This company still uses traditional or the Ad Hoc method to manage existing risks. The Ad Hoc method is where companies manage risk by relying on the initiative of each employee and relying on corrective compared to mitigation. The type of research used is field research with descriptive qualitative methods. Therefore, this research aims to make a System Design and Risk Management Assessment of PT Logistik Nasional Year 2022-2023 using ISO 31000:2018 guidelines. Based on the assessment results, this company's ten main risks are classified into five categories: system, external, technology, people, and process. After identification and risk analysis have been carried out, these risks are treated to minimize the impact and occurrence of risks to the company. Risk treatment results show three risks with a very low level, two with a low level, and five with a medium level. The previous results show three risks at the high and three at the very high levels. Therefore, this proves a need for ISO 31000:2018 standardized risk treatment at PT Logistik Nasional to minimize all risks and impacts.